Implementation of Learning Management System (Lms)-Based Curriculum in Course and Training Institutions in Tegal City: A Theoretical Study - Dewi Apriani Fristianingroem (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
In the digital era, information and communication technology plays a crucial role in supporting the educational process. One of the widely used technological innovations is the use of LMS (Learning Management System). This article discusses the implementation of a Learning Management System (LMS)-based curriculum at Tegal's Vocational Training Institutes (LKP). LMS is expected to enhance the effectiveness of nonformal education by providing flexibility, efficiency, and relevance to workforce needs. Using a qualitative method with a literature review approach, this study identifies the benefits, challenges, and recommendations for LMS implementation. Findings indicate that LMS supports project-based learning and the Merdeka Curriculum but faces obstacles such as limited technological access, low digital literacy, resistance to change, and implementation costs. Addressing these challenges requires improving technological infrastructure, training educators, providing technical support, developing interactive content, and strengthening funding policies. These measures aim to optimize LMS in fostering inclusive, effective, and relevant education aligned with workforce demands.